2022
DOI: 10.1038/s41467-022-33801-z
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical phenotypes and outcomes associated with SARS-CoV-2 variant Omicron in critically ill French patients with COVID-19

Abstract: Infection with SARS-CoV-2 variant Omicron is considered to be less severe than infection with variant Delta, with rarer occurrence of severe disease requiring intensive care. Little information is available on comorbid factors, clinical conditions and specific viral mutational patterns associated with the severity of variant Omicron infection. In this multicenter prospective cohort study, patients consecutively admitted for severe COVID-19 in 20 intensive care units in France between December 7th 2021 and May … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 26 publications
4
46
0
1
Order By: Relevance
“…In a French multicenter prospective cohort study of critically ill patients admitted for severe COVID-19 between December 2021 and May 2022, those infected with Omicron variant were immunocompromised patients in 43% of cases, half of whom had received an organ transplant. This figure was three times higher than Delta-infected patients ( de Prost et al, 2022 ). Their day-28 mortality rate was 47%, significantly higher than that of non-immunocompromised patients (26%).…”
Section: Discussionmentioning
confidence: 58%
“…In a French multicenter prospective cohort study of critically ill patients admitted for severe COVID-19 between December 2021 and May 2022, those infected with Omicron variant were immunocompromised patients in 43% of cases, half of whom had received an organ transplant. This figure was three times higher than Delta-infected patients ( de Prost et al, 2022 ). Their day-28 mortality rate was 47%, significantly higher than that of non-immunocompromised patients (26%).…”
Section: Discussionmentioning
confidence: 58%
“…Hypertension remains a significant risk factor for COVID-19 severity brought on by different SARS-CoV-2 variants, but only limited studies have investigated the relationship between hypertension and infection with these variants. Although the COVID-19 severity and mortality rate associated with Omicron infections declined significantly compared to the previous variants, a recent study showed those infected with variant Omicron were older and had significantly more frequent comorbidities, including hypertension [293] , which is probably due to the remarkably higher transmissibility and immune evasion ability.…”
Section: The Role Of Counter-regulatory Ras To Link Hypertension and ...mentioning
confidence: 91%
“…This method has been previously used for disease phenotyping, such as chronic obstructive pulmonary disease (COPD) ( 11 ) and sepsis ( 12 ). Similarly, several authors have recently used clustering to identify clinical phenotypes in patients with COVID-19 ( 13 21 ).…”
Section: Introductionmentioning
confidence: 99%